2012
DOI: 10.4102/jsava.v83i1.104
|View full text |Cite
|
Sign up to set email alerts
|

Extraskeletal osteochondroma on a cat´s elbow

Abstract: A solitary extraskeletal osteochondroma was diagnosed in a 6-year-old, castrated male Burmese cat, positive for feline leukaemia virus (FeLV). The cat presented with a rapidly growing, solid, non-painful mass on the craniolateral aspect of the left elbow. Radiographs revealed an oval, well circumscribed 2.0 cm × 1.5 cm × 1.5 cm mineralised mass separated from the underlying bone. Surgical excisional biopsy confirmed the diagnosis. Feline extraskeletal osteochondromas are benign tumours frequently seen in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 15 publications
1
17
0
3
Order By: Relevance
“…This suggested the involvement of FeLV in the tumor induction, mainly when considered the cat's age; it was younger than described for osteochondroma in this species. Some authors suggested that FeLV may be related to the etiology of feline osteochondromas (POOL & CARRIG, 1972;DOIGE, 1987;ROSA & KIRBERGER, 2012), and viral particles have been observed in proliferated chondroblast membranes (POOL & CARRIG, 1972). However, mechanisms of invasion and the pathogenesis of this disease have not been fully elucidated (POOL & CARRIG, 1972;DOIGE, 1987;ROSA & KIRBERGER, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…This suggested the involvement of FeLV in the tumor induction, mainly when considered the cat's age; it was younger than described for osteochondroma in this species. Some authors suggested that FeLV may be related to the etiology of feline osteochondromas (POOL & CARRIG, 1972;DOIGE, 1987;ROSA & KIRBERGER, 2012), and viral particles have been observed in proliferated chondroblast membranes (POOL & CARRIG, 1972). However, mechanisms of invasion and the pathogenesis of this disease have not been fully elucidated (POOL & CARRIG, 1972;DOIGE, 1987;ROSA & KIRBERGER, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…One type of neoplasm is an osteochondroma, which is a benign primary bone tumor that originates from the bone surface to form a projection covered by cartilage (THOMPSON & POOL, 2002). This tumor can be formed by one or more masses; in the latter case, it is referred to an osteochondromatosis or multiple cartilaginous exostoses (ROSA & KIRBERGER, 2012). In cats, osteochondromas have been linked to feline leukemia virus (FeLV) infections (POOL & CARRIG, 1972;THOMPSON & POOL, 2002;ROSA & KIRBERGER, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations